A metal belt in the Orumiyeh museum, Iran - Khanmohammadi, Behrouz; Bonfanti, Annarita S.; Abbaszadeh, Maryam; Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
This article discusses a bronze belt kept in the Orumiyeh Museum. The belt, almost completely preserved, has a geometric decoration consisting of five parallel bands filled with small embossed dots: this kind of decoration has many parallels spread from the Southern Caucasus to the north-western region of Iran (mainly from the site of Hasanlu). In this contribution, the authors analyse the belt’s morphology and decoration, and identify a series of finds that resemble this specimen, proposing in the end a possible local origin for this kind of motif.